Labeling and Filtering of Medical Information on the Internet - Eysenbach, G.; Diepgen, T. L. (Methods of Information in Medicine, 1999)
Internet information undergoes no quality controls and virtually anybody can publish anything. Because of this, it is difficult for searchers to take information retrieved from the Internet at face value. A related problem is the uncontrolled promotion of medical products on the Internet. A further problem of today’s Internet is that authors use no uniform keywords and other descriptive labels, which deteriorates the quality of search results. A solution for all these problems could be widespread use of descriptive and evaluative metainformation associated with medical Internet information. Our concept is based on a recently established infrastructure for assigning metadata to Internet information, the so-called PICS Standard (Platform for Internet Content Selection). We prototyped a PICS-based rating vocabulary for medical information (med-PICS), containing descriptive and evaluative categories, to be used by the webauthor and third-party label services (such as medical associations), respectively. We propose an international effort to assign metadata to medical Internet information.
Keywords: Public Health; Computer Communication Networks; Standards; Information Services; Quality Control